Child Custody Rights After Parental Divorce in the Marriage Law - Elias Suranta Torong; Junifer Dame Panjaitan (Jurnal Restorasi : Hukum dan Politik, 2023)
If the household situation is no longer harmonious, there is a high possibility of conflict and disputes arising. Resolving major conflicts may be difficult, increasing the possibility that household circumstances contributed to the divorce. Legal rights of minor children after divorce: It is the obligation of parents to fulfill their responsibilities in providing optimal care and education for their children. According to Article 41 of the Marriage Law, it is stated that the father is responsible for all costs related to the child's care and education. In the event that the father is unable to fulfill his responsibilities, the court has the authority to allocate a portion of the child's essential care and education costs to the mother. This responsibility remains even if the parents divorce.